Between the living and the dead : a perspective on witches and seers in the early modern age - Pócs, Éva (Central European University Press ; Distributed in the U.S. by Cornell University Press Services, 1999)
Éva Pócs, one of the most highly respected scholars of historical anthropology, has undertaken extensive research on the history of folk beliefs connected with communication and the supernatural sphere. In this book, she examines the relics of European shamanism in early modern sources, and the techniques and belief-systems of mediators found in the records of witchcraft trials from the sixteenth to the eighteenth century. The book explores the various communication systems known to early modern Hungarians, describes the role of these systems in everyday village life, and shows how they were connected to contemporary European systems, as well as new types of mediators and systems which function right up to the twentieth century. Representing a major contribution to the most up-to-date international research, Eva Pócs draws on significant East European material and literature not previously co-ordinated with that from the West.